Analisis Pengelolaan Sampah Non Medis Kategori Sampah Organik Dan Anorganik Berdasarkan Permenkes No.7 Tahun 2019 Di RS Citra Arafiq Pada Tahun 2022 - Laras Agesti Ayu (Lembaga Pengembangan Kinerja Dosen, 2023)
Based on data on waste generation in the Citra Arafiq Hospital environment in 2022, namely, the average generation of infectious waste is approximately 58.85 kg/day which is transported to TPS, while non-medical waste generated from black plastic bags is approximately 130 .9 kg/day. The success of the waste management system is closely related to the procedures owned by the hospital concerned as a reference for waste management based on PERMENKES No.7 of 2019. The puprose of this research is to analyze Non-Medical Waste Management for Organic and Inorganic Waste Categories based on PERMENKES No.7 of 2019 at Citra Hospital Arafiq in 2022. This study uses a descriptive analytic research with a qualitative approach. Data collection through observation, interviews, and document review. Respondents in this study included 1 key informant, 1 main informant, 4 supporting informants. The research results show that there is no different container between organic and inorganic waste, there is still more than 2/3 of waste found in the container that has not been transported before the time of transportation. the behavior of officers who still mix medical waste with non-medical waste in one transport trolley, and waste collectors who do not use PPE completely. Still found black plastic that has not been tied or tightly wrapped at TPS, based on interviews, often the garbage is forgotten to be transported.